2017
DOI: 10.3168/jds.2016-11909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding strategies and cropping systems on greenhouse gas emission from Wisconsin certified organic dairy farms

Abstract: Organic agriculture continues to expand in the United States, both in total hectares and market share. However, management practices used by dairy organic producers, and their resulting environmental impacts, vary across farms. This study used a partial life cycle assessment approach to estimate the effect of different feeding strategies and associated crop production on greenhouse gas emissions (GHG) from Wisconsin certified organic dairy farms. Field and livestock-driven emissions were calculated using 2 dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
6
0
1
Order By: Relevance
“…However, some SCS studies showed a loss of soil carbon instead of SCS for a variety of cropping systems (e.g. 130,138,142 ). Further, most studies reported total carbon emissions for the entire product system, but not negative carbon emissions due to SCS as such.…”
Section: Soil Carbon Sequestration (Scs)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, some SCS studies showed a loss of soil carbon instead of SCS for a variety of cropping systems (e.g. 130,138,142 ). Further, most studies reported total carbon emissions for the entire product system, but not negative carbon emissions due to SCS as such.…”
Section: Soil Carbon Sequestration (Scs)mentioning
confidence: 99%
“…123,124,135 ) or economic value (e.g. 117,130 ). For cropping systems, allocation was usually not required with gate-to-gate system boundaries, since the only function was to deliver the feedstock to the farm gate.…”
Section: Soil Carbon Sequestration (Scs)mentioning
confidence: 99%
“…However, research on nutrition, genetics, and whole-farm systems is needed to guide farmers' decisions on how to best feed and breed to optimize forage DMI and milk production while reducing the environmental impact of organic dairies. Liang et al (2017), using the integrated farm systems model (Rotz, 2013), showed that greenhouse gas emissions per tonne of ECM, with or without accounting for soil carbon change, were greatest in organic dairy farms belonging to cluster 2 followed by clusters 4, 1, and 3. Their whole-farm modeling simulations indicated that more greenhouse gas was emitted into the environment the longer the cows had access to pasture during the grazing season (Liang et al, 2017).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Liang et al (2017), using the integrated farm systems model (Rotz, 2013), showed that greenhouse gas emissions per tonne of ECM, with or without accounting for soil carbon change, were greatest in organic dairy farms belonging to cluster 2 followed by clusters 4, 1, and 3. Their whole-farm modeling simulations indicated that more greenhouse gas was emitted into the environment the longer the cows had access to pasture during the grazing season (Liang et al, 2017). Grass-fed organic dairies use nutritional and management strategies that resemble those adopted by farms in cluster 2 (Hardie et al, 2014;Liang et al, 2017) except the lack of concentrate.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation